2015
DOI: 10.1159/000440724
|View full text |Cite
|
Sign up to set email alerts
|

Gly388Arg FGFR4 Polymorphism Is Not Predictive of Everolimus Efficacy in Well-Differentiated Digestive Neuroendocrine Tumors

Abstract: Introduction: Preclinical data suggest that the single nucleotide polymorphism substituting a glycine for an arginine in codon 388 of the FGFR4 transmembrane domain may increase the proliferation of xenografted neuroendocrine cell lines and decrease their sensitivity to everolimus by modulating STAT3 signaling and the mTOR pathway. Aim: To evaluate the prognostic and predictive values of this polymorphism on everolimus efficacy in patients treated for digestive neuroendocrine tumor (NET). Patients and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Another study genotyped the fibroblast growth factor receptor 4 (FGFR4) using DNA isolated from tissue or blood in panNETs, and found that patients homozygous for FGFR-G388 demonstrated greater tumor shrinkage with everolimus treatment than those harboring only one FGFR4-R388 allele[142]. Although longer PFS and OS were also observed in those homozygous for FGFR4-G388, these were not statistically significant due to small number of patients, which is consistent with the result from another group showing that FGFR4 polymorphism did not have predictive value on everolimus treatment[143]. …”
Section: Markers Predicting Efficacy Of Everolimussupporting
confidence: 63%
“…Another study genotyped the fibroblast growth factor receptor 4 (FGFR4) using DNA isolated from tissue or blood in panNETs, and found that patients homozygous for FGFR-G388 demonstrated greater tumor shrinkage with everolimus treatment than those harboring only one FGFR4-R388 allele[142]. Although longer PFS and OS were also observed in those homozygous for FGFR4-G388, these were not statistically significant due to small number of patients, which is consistent with the result from another group showing that FGFR4 polymorphism did not have predictive value on everolimus treatment[143]. …”
Section: Markers Predicting Efficacy Of Everolimussupporting
confidence: 63%
“…These patients showed a reduction in everolimus treatment response. On the contrary, in 2016, Cros et al evaluated the prognostic and predictive value of the FGFR4 Gly388>Arg388 mutation in everolimus efficacy in a NET cohort (Cros et al 2016). This study did not confirm the mutations' prognostic nor its predictive value.…”
Section: Genetic Alterations In Growth Signaling Receptorsmentioning
confidence: 84%
“…TSC-2, PTEN), a frequent finding in pNET tumor samples, might be more indicative of tumor response although correlative data to everolimus efficacy are lacking (Missiaglia et al 2010). Different variables have been tested for their predictive value (the occurrence of stomatitis, an early decrease of circulating chromogranin A and the FGFR4 genotype polymorphism), but none of them represents a definite predictor of response to everolimus (Yao et al 2011a, Serra et al 2012, Cros et al 2016, Rugo et al 2016.…”
Section: :11mentioning
confidence: 99%